Effect of discards on roundnose grenadier stock assessment in the Northeast Atlantic - Pawlowski, Lionel; Lorance, Pascal (Aquatic Living Resources, 2009)
In the Northeast Atlantic fishery for roundnose grenadier Coryphaenoides rupestris, discards account for about 30% of the catch in weight. Data on discards are scarce; however, length distributions and discard rates appear to be relatively stable from year to year. In contrast, landings data available since 1990 show that the average pre-anal fin length has decreased from 20.7 cm in 1990 to 15.2 cm in 2008, resulting in a 58% reduction of the mean individual weight (850 g in 2008) and an increasing occurrence of overlapping class sizes between landings and discards in recent years. For stock assessment, the method of separable virtual population analysis (SVPA) was used. However, because of the lack of discard data for many of the years covered by the study, the catch data used as input to the assessment model had to be reconstructed from the available information (landings, discards, fishing effort and bathymetric distribution of the stock) using two methods. The first method relied on the assumption that the recent length distributions of discards were applicable to the earlier years (1990-1997). It resulted in unrealistic bimodal length distributions, suggesting a change in discarding practices through time, with larger individuals being discarded in the early days. The second method, based on the fishing effort and length distribution by depth strata, produced unimodal distributions for the whole period and confirmed that the average length of discarded fish was higher in the early days of the fishery. In both cases, the estimates of biomass follow parallel trends, suggesting a strong decline in the population. The available information and methods are discussed.